Dilatancy Characteristics and Influencing Factors of Large-Aggregate Core Wall Asphalt Concrete - HE Jian-xin, YANG Han-bing, CHEN Peng-peng, DING Xin-yu, WANG Ya-nan, LIU Liang (长江科学院院报)
[Objective] To promote the application of large-aggregate asphalt concrete in water conservancy projects, this study investigates the stress-strain and dilatancy characteristics of large-aggregate asphalt concrete under the same mix ratio but under varying influencing factors. [Methods] Under large shear deformation conditions (εa=30% ), static triaxial tests were carried out on asphalt concrete with Dmax=26.5, 31.5, and 37.5 mm. The dilatancy characteristics were elucidated from the perspectives of confining pressure and different maximum aggregate sizes. The relationship between the phase transformation stress ratio (Mpt) of asphalt concrete and confining pressure as well as different maximum aggregate sizes was comparatively analyzed, and an expression for determining whether dilatancy occurred in the specimen based on initial parameters was established. To further demonstrate the applicability of large-aggregate asphalt concrete, the Dmax=19 mm asphalt concrete in the core wall was replaced with Dmax=37.5 mm asphalt concrete. Based on a finite element model that ignored the contact and dilatancy between the core wall and the rockfill body, stress-deformation calculations were performed on the asphalt concrete core wall of a typical project in Xinjiang to simulate the behavior of the core wall with large-aggregate asphalt concrete and analyze the influence of maximum aggregate size on the calculation parameters. [Results] (1) With increasing aggregate size, the stress-strain curve of asphalt concrete changed from the softening type to the hardening type. (2) Under the same confining pressure conditions, the tangent modulus Et of large-aggregate asphalt concrete was lower than that of Dmax=19 mm asphalt concrete. As the confining pressure increased, both the maximum deviatoric stress and the maximum volumetric strain of Dmax=37.5 mm asphalt concrete decreased compared to Dmax=19 mm asphalt concrete, indicating that appropriately increasing the maximum aggregate size could weaken the shear dilatancy. (3) An empirical expression for calculating the phase transformation stress ratio Mpt based on initial physical parameters (confining pressure, different maximum aggregate sizes) was proposed, which could serve as a criterion for the transformation between shear contraction and dilatancy in asphalt concrete. A larger Mpt value indicated stronger shear dilatancy. (4) Furthermore, the finite element analysis results showed that there were almost no differences in settlement rate, maximum minor principal stress, and maximum major principal stress of the core walls. The dilatancy characteristics of large-aggregate asphalt concrete met the requirements of high-stress and deep overburden conditions for high dam projects. [Conclusion] Under the conditions of this study, increasing the maximum aggregate size in the asphalt concrete core wall has almost no effect on its stress condition. The experimental results provide a theoretical basis for the promotion and application of large-aggregate asphalt concrete in high dam projects under high-stress and deep overburden conditions.